2018
DOI: 10.1002/joc.5513
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity studies of the RegCM4 simulation in West and central Africa during strong and weak years of Atlantic cold tongue

Abstract: This study evaluates the ability of the Regional Climate Model (RegCM4) to reproduce the observed rainfall and wind over West and central Africa (WCA) during two contrasting years of the Atlantic cold tongue (ACT): the very cold in 1992 and very warm in 2007 depicted by the Caniaux et al.’s index. The convective schemes of Kuo, Massachusetts Institute of Technology‐Emanuel (Ema) and Grell with closure assumptions of Arakawa–Schubert (GAS) and Fritch–Chappel (GFC) were compared and the best scheme was tested to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 95 publications
(146 reference statements)
0
1
0
Order By: Relevance
“…Modelling studies with RCMs carry out over Africa mainly focused either over West Africa (Sijikumar et al, 2006;Diallo et al, 2012Diallo et al, , 2013Gbobaniyi et al, 2014;Klutse et al, 2016;Dieng et al, 2017), East Africa (Anyah and Semazzi, 2007;Endris et al, 2013) or Southern Africa (Vigaud et al, 2012;Diallo et al, 2015;Abiodun et al, 2016;Pinto et al, 2016), where they contributed to improve GCMs simulations. Meanwhile, some studies showed that over CA, RCMs have significant deficiencies associated either to the poor parameterization of internal process or to the very complex and heterogeneous topography of the region which remains a major challenge for the climate modellers community (Tchotchou and Kamga, 2010;Fotso-Nguemo et al, 2016;Mbienda et al, 2016;Vondou and Haensler, 2017;Kenfack et al, 2018;Tamoffo et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Modelling studies with RCMs carry out over Africa mainly focused either over West Africa (Sijikumar et al, 2006;Diallo et al, 2012Diallo et al, , 2013Gbobaniyi et al, 2014;Klutse et al, 2016;Dieng et al, 2017), East Africa (Anyah and Semazzi, 2007;Endris et al, 2013) or Southern Africa (Vigaud et al, 2012;Diallo et al, 2015;Abiodun et al, 2016;Pinto et al, 2016), where they contributed to improve GCMs simulations. Meanwhile, some studies showed that over CA, RCMs have significant deficiencies associated either to the poor parameterization of internal process or to the very complex and heterogeneous topography of the region which remains a major challenge for the climate modellers community (Tchotchou and Kamga, 2010;Fotso-Nguemo et al, 2016;Mbienda et al, 2016;Vondou and Haensler, 2017;Kenfack et al, 2018;Tamoffo et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%